Intracanal Medicaments in Paediatric Endodontics - Praspita Parlin Patro (Indian Journal of Forensic Medicine & Toxicology, 2020)
The basic motive of Paediatric Endodontic Therapy is to remove microorganisms such as bacteria from theroot canal system in which the remaining bacteria cannot survive. Intracanal Medicaments is an imperativestep in killing the bacteria in root canals. Moreover, in Paediatric Endodontic, cleaning & shaping is importantthan intracanal medicaments. The objective of Intracanal Dressing is for a blockade coronal discharge fromthe space between filling materials and cavity walls. For intracanal medicaments, calcium hydroxide mixedwith slim paste is more convenient as it is stable, harmless to the body and bactericidal. If multiple visitsto endodontic are chosen, it is strongly recommended. Therefore, the purpose is to examine the need for anintracanal medicament.